Disposition kinetics and distribution of ciprofloxacin in biological fluids of goats after intravenous administration - SINGH, CHANDR SHEKHAR; SINGH, S D; SINGH, M K; JAYACHANDRAN, C (The Indian Journal of Animal Sciences, 2014)
Pharmacokinetics and distribution of ciprofloxacin in various biological fluids were undertaken post i. v. dose (4 mg. kg-1) in goats. Peak concentrations of 2.53 Â± 0.07, 12.23 Â± 0.82 and 198.50 Â± 25.89 Âµg.mlÂ·’ were attained at 0.083, I and 1 hr in plasma, milk and urine respectively. The therapeutic concentration (â‰¥0.12 I1g.mlÂ·’) were maintained up to 10, 12 and 36 hr, respectively, in plasma, milk and urine. Distribution half life (t1/2Î±) and elimination half life (t,1/2Î²) of 0.32 Â± 0.05 and 4.71 Â± 0.67 hr were noted in the present study. Vd of 4.22 Â± 0.51 L.kg-1 obtained for ciprofloxacin in goat denotes its wide distribution in the body. The present investigation suggests a loading dose (D*) of 4.4 mg.kg-1 followed by a maintenance dose (Do) of 3.8 mg.kg-1 at the dosage interval (Î³) of 12 hr for maintaining therapeutic concentration (MIC) of 0.12 Âµg.mlÂ·-1.